Modulation of Polycystic Kidney Disease by non-coding RNAs - Ramalingam, Harini (Cell Signal, 2020)
PURPOSE OF REVIEW: microRNAs (miRNAs) are a class of small, evolutionarily conserved, non-coding RNAs (ncRNAs) that function as inhibitors of post-transcriptional mRNA expression. They are implicated in the pathogenesis of numerous diseases, including many common kidney conditions. In this review, we focus on how miRNAs impact autosomal dominant polycystic kidney disease (ADPKD) progression. We also discuss the feasibility of the emerging novel antisense oligonucleotides (ASOs) drug class, which includes anti-miRNA drugs, for the treatment of ADPKD. RECENT FINDINGS: Aberrant miRNA expression is observed in multiple PKD murine models and human ADPKD samples. Gain and loss-of-function studies have directly linked dysregulated miRNA activity to kidney cyst growth. The most comprehensively studied miRNA in PKD is the miR-17 family, which promotes PKD progression through the rewiring of cyst metabolism and by directly inhibiting PKD1 and PKD2 expression. This discovery has led to the development of an anti-miR-17 drug for ADPKD treatment. Other miRNAs such as miR-21, miR-193, and miR-214 are also known to regulate cyst growth by modulating cyst epithelial apoptosis, proliferation, and interstitial inflammation. SUMMARY: miRNAs have emerged as novel pathogenic regulators of ADPKD progression. Anti-miR-based drugs represent a new therapeutic modality to treat ADPKD patients.